PKM Pencegahan Stunting melalui Konsumsi Tablet Penambah Darah dalam Prespektif Maqosid Syariah - Hidayah, Wahyudi; Hariyati, Tri; Dwistia, Halen (Yayasan Daarul Huda Kruengmane, 2025)
In the village gapura Kotabumi there are still relatively many stunting. Stunting becomes importen to be handled because it involves the quality of human ressources. Stunting in addition to the resk of physical growth retardation and susceptibility to disease, also causes cognitive developmental barriers that will affect the level of intelligence and productivity of children in the future. The causes are lack of food intake, presence of infectious diseases, mother’s lack of knowledge about stunting, wrong parenting, poor sanitation and low health services. In addition, the community has not realized stunting children as a problem, because stunting children in the community are seen as children with normal activities. By looking at the problem of these partners, this community partnership program aims to provide knowledge an information to the community in order to prevent and overcome stunting problems. The results achieved in this community partnership program, namely, participants have knowledge about: (a) the meaning and characteristics of stunting; (b) the factors that cause stunting; (c) the infact of stunting; (d) how to prevent and overcome stunting; and (e) how to improve the quality of nutrition services for children.